CAFFEINE CONSUMPTION HABITS AND PERCEPTION OF ADOLESCENTS IN CHENNAI POPULATION* - T, PriaDarsini; R, Gayatridevi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Caffeine consumption by adolescent population has increased dramatically over the last decade through increased coffee consumption and energy drinks. However, caffeine causes many adverse effects, which demands people’s attention. The purpose of this study was to determine the most popular caffeinated product among adolescents and the knowledge and belief of adolescents about caffeine in their day to day life. Methods: An online survey was created and about 260 responses were obtained. Only 248 were counted as the remaining was removed by exclusion criteria. Results: The most popular caffeine intake by adolescents was coffee. Students ingested caffeine at levels that could cause negative health effects and seemed unaware of the total amount of caffeine consumed. Conclusion: More information about caffeine should be incorporated into health education at all levels, so students can identify and avoid negative effects along with caffeine withdrawal and addiction. Keywords: Caffeine, Coffee, Adolescents, Addiction, Habits.